Preliminary studies on feline coronavirus distribution in naturally and experimentally infected cats - KISS, I. (Res Vet Sci, 2000)
The shedding, tissue distribution and quasispecies composition of feline coronaviruses were studied in naturally and experimentally infected cats. The infection remained subclinical, but the majority of the animals shed the virus via faeces throughout the experiment. Sequences corresponding to the viral nucleocapsid region were amplified by reverse-transcription polymerase chain reaction from the cortex, dura mater, pancreas, lungs, third eyelid, and the heart muscle in four cases. Interestingly, the ORF7b viral region – a supposed virulence factor – was detected in fewer organs, raising the possibility that this region can be affected by deletions during virus replication in vivo. It is demonstrated that the composition of the viral quasispecies differs between organs, and that genomic regions with different functions undergo distinct processes of selection, which should be considered during the evolution of feline coronaviruses.